(untitled) (Rudarsko-geološko-naftni zbornik, 2016)
The Istrian coal mines, located in the eastern part of the Istrian Peninsula (Northern Adriatic Sea, Croatia) had by far the most important and economically the most valuable deposits of the anthracite coal reserves in Croatia since the 18th century until the year 1999, when their excavation and use in the coal-fired power plant Plomin ceased. The coal is found within the Palaeocene Kozina limestone beds. Four coal basins, Karojba, Sveti Martin, Pićan, and the Labin basin, hosted seven coal mines, e.g. Tupljak, Potpićan, Kozljak, Štrmac, Raša, Ripenda, and Krapan. The coal has been generally known under the name of Raša coal. It is exceptional in world terms due to its high content of organic sulphur, which can be up to 14%. Herewithin, this paper reviews Croatian scientific publications devoted to various aspects of Raša coal, along with the most important publications on either similar coals or relevant subjects worldwide. A brief introduction deals with the role of coal in electricity production, and the history of coal mining in Istria. The following chapter summarises current knowledge of the coal sulphur geochemistry, with several examples of high-sulphur coals from India and China. It is followed by the geological, geochemical, and physical characterisation of Raša coal. Since perturbations to ecosystems caused by coal combustion have been documented in numerous papers from a number of countries, Croatian studies carried out to determine the impact of Raša coal combustion on the local environment are also presented.